Effects of Soil on Sissoo (Dalbergia Sissoo, Roxb.) Growth in a Plantation Forest of Nepal - Sah, S. P.; Upadhyay, S. K.; Pandit, P.; Lilles, J. B. (Indian Forester, 2003)
The present paper deals with the assessment of the spatial variations of the physical characteristics of soil in a 6 years old Dalbergia sissoo, Roxb. Plantation site (area 2.3 hal of Nepal. This plot has been established with seedlings propagated from the seeds of 84 superior phenotypes selected across the species natural range in Nepal. The purpose of the research plot has been to develop breeding strategies for sissoo in Nepal and to identify and conserve superior genotypes that could be used in the next breeding cycle (second generation). The pH of the top-soil ranged from 4.5 to 5.5 but this difference was not statistically significant. The soil colour was found to be homogenous and it was dark grey-brown in the top-soil and yellowish brown in the sub-soil. In the plot, the soil texture ranged from clayey-loam to clayey in the top.soil, whereas it is silty-loam in the sub-soil. No significant variations among family plots with respect to their soil texture and pH (top.soillayer) were found. D. sissoo growth, at this plot, varied significantly, ranging from 2.5 m to 13 m. The present study concludes that the variations in tree growth in the plots has been due to the water logging in those plots. The water-logged plots have much more clay-content than that in the other plots. Moreover, the plots with sandy soils have normal tree growth in majority of the plots.